The Effect of Academic Resilience and Social Support towards Student Involvement in Online Lecture - Rabiatul Adhawiyah; Diah Rahayu; Aulia Suhesty (Gadjah Mada Journal of Psychology (GamaJoP), 2021)
The Covid-19 pandemic has made conventional lectures turn to online learning. The lecture system that is carried out by students is expected not to reduce student engagement in every lecture. Student involvement is due to the social support and academic resilience of students. This study aimed to determine the effect of academic resilience and social support on student engagement in online lectures. This study used a quantitative approach. The subjects of this study were 100 students of the Faculty of Social and Political Sciences, Mulawarman University who were selected using a simple random sampling technique. The data collection method used the scales of student engagement, academic resilience, and social support. The results showed that: (1) there is a significant effect of academic resilience and social support on student involvement in online lectures (p < 0.05) and had an influence contribution (R2) of 52%; (2) there is a significant positive effect of academic resilience on student involvement in online lectures (p < 0.05); (3) there is a significant positive effect of social support on student involvement in online lectures (p < 0.05).